Spontaneous Bladder Perforation in a Patient with a Long-Term Intraurethral Catheter - Taegi Choi; Hyunkyung Lee; Junseok Kim; Sunghoon Lee; Younkyung Cho; Eunyoung Kang; Jinsun Kang; Sumin Lee; Eunju Na (Urogenital Tract Infection)
Urinary catheters are commonly used to address various urinary problems. However, the catheter itself can be a cause of several complications, including catheter-associated urinary tract infections, damage to the bladder and kidneys, and, in extremely rare cases, bladder perforation. We present a case of spontaneous bladder perforation in a patient who had a long-term indwelling intraurethral catheter. The patient with prior hypoxic brain damage suddenly developed tachypnea, tachycardia, and oxygen desaturation. Computed tomography and retrograde cystography revealed an extraperitoneal bladder perforation with an intra-pelvic abscess. Antibiotics were prescribed and a urinary catheter was inserted for drainage. After 11 weeks, the abscess resolved, and the catheter was removed to enable self-voiding. The perforation was attributed to chronic inflammation and distension of the bladder wall caused by the intraurethral catheter. Given the potential complications associated with long-term urinary catheterization, the timely removal of indwelling catheters should be considered.